Modifikasi Pakan Buatan untuk Meningkatkan Pertumbuhan dan Kelangsungan Hidup Udang Windu (Penaeus monodon) - Awaludin Awaludin; Ricky Febrinaldy Simanjuntak; Jumsan Jumsan (Fakultas Biologi | Universitas Jenderal Soedirman, 2020)
Nutrition for the growth of black tiger shrimp (Penaeus monodon), include protein, carbohydrate, fat, minerals and vitamins. One of the local raw materials that can be utilized is seaweed (Kappaphycus alvarezii) as an additional ingredient in making artificial feed. This study aims to determine the effect of artificial feeding mixed with seaweed meal on the growth and survival of tiger shrimp. This research is experimental with treatment A: Control, treatment B: 10 grams (seaweed flour), treatment C: 30 grams (seaweed flour), treatment D: 50 grams (seaweed flour) with 5 replications. Treatment D showed the highest growth rate of an average weight of 0.169 grams and an average length of 1.95 cm, the SR of each treatment did not differ significantly. The addition of seaweed flour gives a significant value to the growth of tiger prawns.